Anisotropic photoresponse behavior of a LaAlO3 single-crystal-based vacuum-ultraviolet photodetector. Issue 45 (9th November 2022) - Sun, Xiyu; Wang, Danhao; Memon, Muhammad Hunain; Zhu, Siqi; Yu, Huabin; Wang, Hongxuan; Fang, Shi; Kang, Yang; Liu, Xin; Luo, Yuanmin; Zhang, Haochen; Luo, Dongyang; et al.
Abstract : A vacuum ultraviolet photodetector made of ultrawide bandgap semiconductor LaAlO3 demonstrates an anisotropic photo response behavior under 185 nm light illumination via the precise regulation of the crystal orientations at (100), (110), (111) plane. Abstract : Nowadays, vacuum-ultraviolet (VUV) photodetectors (PDs) have attracted extensive attention owing to their potential applications in space exploration, radiation monitoring, and the semiconductor industry. Benefiting from its intrinsic ultra-wide band-gap, chemical robustness, and low-cost features, LaAlO3 shows great promise in developing next-generation compact, cheap, and easy-to-fabricate VUV PDs. In this work, we report the unique anisotropic photoresponse behavior of LaAlO3 single crystals for VUV photodetection applications. First of all, with the guidance of density functional theory (DFT) calculations along with the comprehensive material characterization, the anisotropic carrier transport behavior of LaAlO3 single crystals was confirmed. Thereafter, after exploring the metal–semiconductor–metal (MSM) device configuration along different substrate orientations, including (100), (110), and (111)-LaAlO3 single crystals, we found that the (110)-LaAlO3 VUV PD exhibits the best device performance under VUV illumination, with a responsivity of 2.23 mA W −1, a high detectivity of 3.72 × 10 11 Jones, and a photo-to-dark-current ratio of 5.48 × 10 3 . This work not only provides a feasible avenue to explore the anisotropic optoelectronic behavior of ultra-wide band-gap semiconductors but also expands the application of the low-cost oxide perovskite family in the field of VUV photodetection.